Betrayal as a crisis of moral authority: the author’s worldview in Sirrul Marquise through Lucien Goldmann’s genetic structuralism - Karisma kamalia; Abdul Basid (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This article aims to examine the author’s worldview toward betrayal in the short story Sirrul Marquise. Before exploring the author’s worldview, this study first discusses the historical and social background that underlies the creation of the work. The study employs a descriptive qualitative research method by textual data analysis and interpretation it through the lens of Lucien Goldmann’s genetic structuralism theory. The data consist of primary sources in the form of the contemporary Arabic  short story titled Sirrul Marquise and secondary data obtained from related journal articles and previous studies. Through this method, the researcher found that Nabil Al-Othmani, the author of “Sirrul Marquise,” was influenced by Morocco’s  social conditions, particularly those related to power struggles and the territorial conflict in the Sub-Saharan region. The short story reflects the author’s worldview on betrayal through four main dimensions: betrayal of social institutions, parental betrayal of children, betrayal of moral and humanitarian values, and betrayal of oneself. Each form of betrayal illustrates a deeper social criticism against the moral decay and crisis of trust in modern Moroccan society. This research contributes to expanding the discourse on betrayal in literary studies, especially within the framework of genetic structuralism, by connecting individual moral collapse to collective social structures. The findings also provide implications for further application of genetic structuralism in modern Arabic literature studies, particularly in works addressing postcolonial identity and social conflict. It is hoped that this study can fill the research gap concerning betrayal in macro social contexts and inspire future studies to explore Goldmann’s theory more comprehensively in various literary works.